Relationship between teacher formative feedback types, self-regulated learning, and perception of feedback among Chinese public middle school students - Mingzhe, Guo; Yasin, Maizura (Human Resource Management Academic Research Society, 2023)
The aim of this study was to determine the relationship between five types of formative feedback, self-regulated learning and perception of feedback and their respective levels. The study used proportional stratified random sampling method to select 558 students from four Chinese public secondary schools in Liaoning Province. A correlational research design was used and descriptive and Pearson correlation analyses were conducted. The results showed that the level of self-regulated learning was at a moderate level, while the other two variables were at a higher moderate level. Furthermore, bivariate correlation analysis indicated that there was a significant positive correlation between verification feedback, directive feedback, scaffolding feedback, teacher praise, self-regulated learning and perceptions of feedback, while there was no correlation for teacher criticism. In conclusion, this result revealed that students perceived the feedback at a higher level but perceived their self-regulated learning at a lower level. Except for teacher criticism, significant positive correlations were found between other formative feedback types and self-regulated learning and feedback perceptions. In practice, teachers should increase scaffolding feedback and teacher praise with task-specific information, and emphasize the development of student responsibility and self-regulated learning, working to create a more equal dialogue between teachers and students.